THE INFLUENCE OF FINANCIAL LITERACY AND ISLAMIC BUSINESS ETHICS ON GREEN ISLAMIC INVESTMENT WITH INVESTOR TRUST AS A MEDIATOR AND SPIRITUAL KNOWLEDGE AS A MODERATOR - Yulius Dharma; Munardi; Anwar Puteh; Aiyub Yahya (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the influence of financial literacy and Islamic business ethics on green Islamic investment by considering investor trust as a mediating variable and spiritual knowledge as a moderating variable. The research was conducted in Bireuen Regency, North Aceh Regency, and Lhokseumawe City, involving 300 respondents from diverse backgrounds, including civil servants, private employees, entrepreneurs, students, and other professions. A quantitative approach with a survey method was employed, and the data were analyzed using Structural Equation Modeling based on Partial Least Squares (SmartPLS). The findings reveal that financial literacy positively affects green Islamic investment and significantly enhances investor trust. Islamic business ethics contribute to strengthening investor trust, although their direct influence on green Islamic investment is relatively limited. Investor trust emerges as a crucial factor in reinforcing the relationship between financial literacy and Islamic business ethics with green Islamic investment, functioning as a mechanism of partial mediation. Furthermore, spiritual knowledge has a direct influence on green Islamic investment and acts as a moderating factor that strengthens the link between independent variables and investment decisions.Theoretically, this study contributes to the literature on Islamic finance and sustainable investment by integrating financial literacy, Islamic business ethics, investor trust, and spiritual knowledge into a comprehensive model. Practically, the findings emphasize the importance of financial literacy education, the application of Islamic business ethics, the cultivation of investor trust, and the reinforcement of spiritual dimensions to foster the growth of inclusive, competitive, and sustainable green Islamic investment.